Parâmetros químicos e qualidade de salsa em função de substratos orgânicos associados ao biochar - Santos, Francielly Torres dos (2016)
Parsley has been widely traded as a flavoring in Brazil and worldwide. The quality to produce salsa depends on its cropping management. This, this study aimed to evaluate the effect of alternative organic substrates in productivity and nutritional quality of Petroselium crispum. The treatments consisted of five organic compounds obtained by agro-industrial waste composting process of broiler production chain in which they varied the main source of carbon, i.e, waste cotton carding, pruning of ground urban trees, sawdust, bagasse of milled cane and ground napier grass. In order to obtain the organic substrates, it was added 0, 15, 30, 45 and 60% biochar to each of the five organic compounds, a charcoal obtained from burning wood in boilers. The experimental design was completely randomized in a 5x5 factorial design, with four replications. The nutritional quality of salsa was determined by N, P, K evaluation, and antioxidant activity and productivity. Concerning substrates, functional groups and determination of humification degree were evaluated, correlated with parsley dry weight. It was concluded that the use of substrate from Napier grass ground does not favor Petroselium crispum production. Adding biochar associated with organic compost from urban tree pruning whose main source is carbon favors flavonoid content of Diosmetin-apiosilglucoside-isomer and apigenin-malonyl-glucoside in Petroselium crispum. The electrical conductivity of the organic substrate is the main factor that contains Petroselium crispum production while addition of biochar can minimize this effect